Pengaruh Big Five Personality Terhadap Disiplin Kerja Pegawai Dinas Pemberdayaan Perempuan dan Perlindungan Anak di Kota Manado - Siti Mahrani M. Rusli; Deetje Josephine. Solang; Meike Endang Hartati (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to determine the effect of big five personality on the work discipline of employees of the women's empowerment and child protection office in Manado city, in this study using causal quantitative research. and the sample taken using a total sample of 112 respondents. The measuring instrument of this research instrument is the big five personality scale based on Costa & Mccrae's theory and the work discipline scale based on Saydam's theory (2007) and the results obtained in this study that Extraversion, Agreablnness, Conscienstious, Neuroticism and Opnnes to Experience from all traits of the big five personality, show that Extraversion traits have a significant value of 0.003 (p < 0.05) and the coefficient value is beta 0.283 which means there is a positive influence on work discipline, and Agreablnnes get a significant value of 0.000 (p < 0.05) and the coefficient value is beta 0.465 which means it shows that Agreablnness traits have a positive influence on work discipline and on Conscienstious traits get a significant value of 0.000 (p < 0.05) and the coefficient value is beta 0.644 which means that Conscientioussness traits have a positive influence on work discipline work discipline while on Neurotcism has a negative influence with a significant value of 0. 002 (p < 0.05) and the coefficient value is beta -0.283 which means Neurotcism has a negative influence on work discipline and Opnnes to Experience shows a significant value of 0.003 (p < 0.05) and the coefficient value is beta 0.283 which means the Opnnes to Experience traits have a positive influence on work discipline